AI teachers (AI-based robots as teachers): history, potential, concerns and recommendations - Malik, Muhammad Abid; Shah, Rehmat (Frontiers in Education, 2025)
Although Artificial intelligence (AI) has been used in education for a long time, its popularity and spread have witnessed exponential growth since the launch of ChatGPT. It can be used as a tool, teaching assistant, or teacher. AI teacher (AI-based robot as a teacher) is not a new concept with the first teaching robots used in the 1970s; however, most of the research and usage of AI in education is focused on AI as a tool or a teaching assistant. This article looks at AI teachers’ history, some key cases, potential and benefits, and concerns and challenges associated with their use in classrooms. Overcoming teachers’ shortage, flexibility, transparency, unbiasedness, and improving students’ motivation were some of their key benefits; while being untested and unreliable, cost, need for specific infrastructure and technical expertise, resistance to change, ethical issues, and fears of dehumanizing and desensitizing students were the main concerns and challenges. We suggest co-teaching with AI teachers using four different approaches. Through them, AI teachers and human teachers can work together in classrooms to maximize the effectiveness of the teaching-learning process.